2017
DOI: 10.1002/eat.22697
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle loss and resumption among patients with anorexia nervosa spectrum eating disorders: Is relative or absolute weight more influential?

Abstract: These findings add to the literature indicating that relative and absolute weight status are dual indicators of illness severity in AN, and preliminarily suggest that a large proportion of adults who present for treatment initially may have shown symptoms of starvation at a normal BMI. Results underscore the need to focus on weight loss in early detection efforts and may inform target weight setting in the treatment of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…One study, for example, found that a 5% weight loss in combination with significant ED-related cognitive concerns (i.e.., undue influence of weight on self-evaluation and fears of weight gain) was a marker for a clinically meaningful restrictive eating disorder [ 50 ]. This also concurs with increasing evidence suggesting the importance of assessing relative weight status and weight history, not simply the current weight of the individual, when determining health status and treatment needs [ 51 ] [ 3 ].…”
Section: Discussionsupporting
confidence: 83%
“…One study, for example, found that a 5% weight loss in combination with significant ED-related cognitive concerns (i.e.., undue influence of weight on self-evaluation and fears of weight gain) was a marker for a clinically meaningful restrictive eating disorder [ 50 ]. This also concurs with increasing evidence suggesting the importance of assessing relative weight status and weight history, not simply the current weight of the individual, when determining health status and treatment needs [ 51 ] [ 3 ].…”
Section: Discussionsupporting
confidence: 83%
“…A severity rating scheme for AN based on current BMI may also eclipse the importance of prior weight history, which is of particular salience for adult populations. Increasing evidence suggests that rate of weight loss and relative weight status are important to consider, in addition to absolute or current weight (Bachmann et al 2016;Berner, Feig, Witt, & Lowe, 2017). For instance, overweight patients who develop AN via rapid weight loss may be medically unstable despite falling into the mild severity range (Lebow, Sim, & Kransdorf, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, adaptation to energy deficit can maintain body weight at the expense of energy‐consuming physiological functions such as reproduction 14 . Indeed, BMI was ‘normal’ at the time of first amenorrhoea in 38.5% of 69 women with AN, 15 highlighting the need to quantify weight loss in addition to only BMI at presentation 16 . Furthermore, one third of athletes had amenorrhoea despite ‘normal’ BMI (21.3 ± 1.6 kg/m 2 ), 17 whereas two thirds of women with AN had amenorrhoea at a BMI between 17 and 18.9 kg/m 2 4 .…”
Section: History and Examinationmentioning
confidence: 99%